AB0354 Adult onset still's disease (AOSD):A report of 30 cases. (23rd January 2014) - Tejera, B.; Grados, D.; Martinez-Morillo, M.; Riveros, A.; Rodriguez, S.; Mateo, L.; Holgado, S.; Olivé, A.; Tena, X.
Abstract : Background: Adult Onset Still's disease (AOSD) is a rare systemic disease of unknown etiology, characterized by fever peaks with a evanescent rash, arthritis and/or arthralgia that is associated with odynophagia, lymphadenopathy and hepatosplenomegaly. Laboratory test usually present with leukocytosis, neutrophilia, anemia and an increased in acute phase reactants. There is no pathognomonic laboratory test. Diagnosis is difficult and exclusion of other diseases is requered. Objectives: To describe the clinical characteristics, treatment and outcome of a series of patients diagnosed with adult Still's disease. Methods: Retrospective (1978-2011). UniversityHospital with a referal area of 800, 000 inhabitants.We reviewed the medical records of patients from the database service of Rheumatology. Inclusion criteria: Yamaguchi criteria. Results: Thirty one patients were diagnosed: 9 men (30%) and 21 women (70%). The mean age at diagnosis was 39.9 years (16-68). All had fever associated with rash, except for 3 patients who were enrolled without a rash. The odynophagia was presented in all cases except 1. Polyarticular pattern predominated (22 patients, 73.3%) compared to oligoarticular (3 patients, 9.7%); in 5 patients was not found arthritis, however, arthralgia were seen in 96.7% of cases. Twelve patients had lymphadenopathies and eleven, splenomegaly. Seven patients had both clinical signs. Serositis was uncommon, affecting only 3 patients. Laboratory findings were as followed: leukocytosis with neutrophilia (22 patients, 73.3%), anemia with hemoglobin ≤12 g/dl (15 patients, 50%), with mean hemoglobin of 11.5g/dl, transaminitis (9 patients, 1%), high ferritin with an average of 6614 ng/ml in 19 patients (63.3%). The ESR was determined in 29 patients and was founded elevated in 24 (80%), with a mean of 77.4±39.8 mm in the first hour. C Reactive Protein was determinedin 26 cases, being elevated in 21 patients (70%).Joint radiographswere performed according to articular involvement and remained normal in 23 patients (76.7%). The treatment was: aspirin and/or NSAIDs (90%), corticosteroids (76%), other disease-modifying drugs, 15 patients (76.7%); biological drugs, 6 patients (20%). Mean follow-up: 88 months. The form of evolution of the disease was polycyclic in 15 patients (50%) and monocyclic on the other half of patients. Remission during follow-up was presented in 27 patients (93.1%). Conclusions: The clinical and laboratory characteristicsof this series, did not differ from those reported by other authors. All in all Adult Onset Still's disease responded to treatment. Biological drugs was required in one third of patients. Disclosure of Interest: None Declared